The search for an AIDS vaccine : ethical issues in the development and testing of a preventive HIV vaccine - Grady, Christine (Medical ethics series., 1995)
Efforts to halt the spread of AIDS have failed so far, and the creation of a vaccine seems the best hope for controlling the disease. Yet the process of developing and testing an HIV vaccine raises a host of difficult ethical issues. Describing the role of vaccines in controlling infectious disease, this study surveys the guidelines, regulations, and attitudes concerning human-subjects research. There is current information on the state of HIV research and the challenges facing scientists. Vaccine research differs considerably from drug research, and Grady explores the current wisdom governing research with human subjects. Proposing a model for the ethical conduct of vaccine research in general, this book applies it to the complex case of an HIV vaccine. Clinical trials are already ongoing, and the next step, field trials to determine efficacy, involves another set of issues - and a call for new strategies for ethical conduct. The Search for an AIDS Vaccine is essential reading for everyone interested in ethics and the conduct of HIV vaccine research.